Mengidentifikasi Kebutuhan Informasi untuk Perancangan Panduan Geografis dalam Al-Qur’an - Nurul Khairat (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This research is a study that describes the information needs of users in the design of geographical guides in the Qur'an. The purpose of this research is to identify user information needs for the design of geographical guides in the Qur'an. Geographical information in the Qur'an has historical, theoretical, and practical values that can educate Muslims to understand the relationship between geographical location and Islamic history. This research uses a descriptive qualitative method with an approach to user needs analysis. Data is obtained based on interviews with users who potentially need this information. In addition, data was obtained based on the Qur'an, books, books, internet searches, and others. The results showed that users need a geographical guide in the Qur'an that presents information about geographical locations mentioned in the Qur'an in a visual and interactive way, such as accompanied by visualization of the location discussed, a brief description equipped with interpretation of the Qur'anic verse. In addition, accessibility and accuracy of data are also important aspects in the development of this guide. Understanding the information needs of users can be the basis for designing geographical guides in the Qur'an that are more informative, educative, easily accessible, and obtain user satisfaction.